Ledinflammationer på häst och intraartikulär behandling med hyaluronsyra : en pilotstudie på hyaluronsyra X - Thorell, Karin (SLU/Dept. of Clinical Sciences (until 231231), 2007)
Traumatic arthritis is a common cause of lameness in horses. One of different treatment alternatives of arthritis, is intra-articular injection with hyaluronan. As knowledge about pathophysiology of arthritis and function of hyaluronan is increasing, understanding grows about the mechanism of hyaluronan action in joints. Hyaluronan has, in addition to effects on viscosity, anti-inflammatory and analgesic effects. Extensive research and scientific studies have been made on exogenous hyaluronan. Still, there are questions to be answered about e.g. the importance of molecular weight on hyaluronan effect. Some scientific results say that higher molecular weight hyaluronan has an extended duration in the joint, compared to lower molecular weights. No studies on a product containing hyaluronan molecules with size > 10 × 106 Da, have earlier been made.